EARLY DETECTION OF ALZHEIMER’S DISEASE IN THE MILITARY POPULATION & PUBLIC HEALTH FIELD EXPERIENCE: HIV PREVENTION USING PRE-EXPOSURE PROPHYLAXIS - Cepeda, Ileana (My University, 2017)
Globally there has been approximately 35 million deaths because of the human immunodeficiency virus (HIV) since the start of this epidemic and it is still an ongoing battle (WHO). Research continues in the hopes to stop this epidemic and the development of pre-exposure prophylaxis might be the key to this problem. Pre-exposure prophylaxis--PrEP--is an HIV prevention tool that was approved by the U.S. Food and Drug Administration in 2012. It is an intervention tool developed for those who are at high risk of acquiring HIV. In my field experience, at the Kansas Department of Health and Environment, I was able to create a PrEP toolkit which consisted of educational materials for providers and consumers on PrEP. The overall goal of this field experience is for Kansans to have the opportunity to use PrEP as a prevention tool which may lead to a decrease of HIV cases per year in the state of Kansas. Furthermore, my capstone project focused on Alzheimer’s disease (AD) within the military population. Alzheimer’s disease is a neurodegenerative disease that is currently affecting more than five million Americans. The aging military veterans are one of the populations most affected with Alzheimer’s disease. Evidence suggest that this aging military population has potentially been subjected to additional risk factors compared to the general population. Consequently, it is believed that this population represents an elevated risk for AD and other dementias. Therefore, the goal of our study was to use existing statistical classification methods to be able to detect AD at an early stage and determine important biomarkers for the military population.
Keywords: HIV; AIDS; pre-exposure prophylasia; Alzheimer's Disease; Traumatic Brain Injury; PTSD